Perceptions and Experiences on Wearing Removable Acrylic Denture of Elderly in Bangkruai District, Nonthaburi Province: Phenomenological Research - Thoeprasert, Dulyarat; Radabutr, Matanee (Journal of The Royal Thai Army Nurses, 2023)
This phenomenological research aims to study perceptions and experiences on wearing removable acrylic dentures of the elderly at Bangkruai Hospital. 25 elderly persons wearing removable acrylic dentures were selected using purposive sampling. The data was collected by using in-depth interview questions until data saturation. The data was analyzed by transcribed verbatim and content analysis. The results showed that the elderly provided the meaning of wearing removable acrylic dentures that “a dental appliance used to designate an artificial replacement for the natural teeth, and improves aesthetic appearance, also able to be removed for cleaning”. The seven main issues that emerged from the perceptions and experiences on wearing removable acrylic dentures of the elderly include 1) the problems before wearing the removable acrylic denture, 2) the helping digestive system, 3) the improvement of appearance, 4) the uncomfortable of wearing the dentures, 5) the speaking or pronunciation, 6) the reception of information, and 7) the maintenance of the removable acrylic denture. It is recommended that perceptions and experiences on wearing removable acrylic dentures of the elderly play a significant role in developing a wearing the removable acrylic denture model and provide knowledge to be a guideline for the patients after wearing the denture. An interprofessional practice also plays a crucial role for the elderly after wearing the denture to arrange the appointment to follow up and to solve or prevent the denture problems, and increase the quality of wearing the denture for the elderly.